Evaluating the impact of performance appraisal on doctor’s task and contextual performance: A view of public sector hospitals in Karachi, Pakistan. - Bibi, Munaza; Rafique Ahmed Khan (International Journal of Endorsing Health Science Research, 2021)
Background: Performance appraisal is an essential function implemented by the healthcare organization to gauge an individual's performance while delivering quality care. The present study aimed to evaluate the interrelationship between appraisal and the doctor’s task performance measures. Methodology: A causal study was conducted on a sample of 270 doctors working at Dr. Ruth Pfau Civil Hospital and Jinnah Postgraduate Medical Centre (JPMC) in Karachi, using a deductive approach. An adapted questionnaire was used to examine the specified variables concerning appraisal, task and contextual performance. The collected data was examined using Analysis of Moment Structures (AMOS) and SPSS version 20.0. Results: There was a significant impact of performance appraisal on doctor’s task performance and contextual performance as indicated by the study results. A moderate significant relationship was observed between performance appraisal and doctor’s task performance (r = 0.383; p<0.01), while a strong significant relationship was detected between performance appraisal and doctor's contextual performance (r=0.874; p<0.01). Conclusion: It is concluded that the implemented performance appraisal practices influence doctor's task performance and contextual performance.